COMBINATION OF SURFACE PARTICLE HEAT TRANSFER AND THE SPH METHOD FOR PHASE CHANGE PROBLEMS - FAIZAL (NIM:20910001); Pembimbing: Dr. Suprijadi, FERRY
SPH method is one of the new effective method for handling numerical difficulties in complex flow simulation. The Lagrangian nature of the method make it easier to handle moving boundary problem. Some recent additional feature such as modified Laplace operator made SPH method has better performance to solve single or multiphase heat equation for non isothermal system. However as many body problem method, it has strong dependency to the number of particle involves in calculation. For N particles the order of operation is N2. One problem in phase change simulation related to the number of particle is to enable heat transfer between phase change system with the environment. To act as heat reservoir the infinite number of gas phase must be added to fill remaining domain of phase change system thus increase the computational cost. To avoid this problem we suggest shell energy transport to the edge and free surface particle so the system can perform heat exchange with virtual environment. For each particle on the free surface or the edge, multiphase conduction governed by Fourier law were applied locally at the same time step with free and forced convection. The simulation performed from zero (pure conduction) to few hundreds value (very effective convection) of Nusselt number. The result show effective Nusselt number which affected heat transfer process ranged from 0 to 160.